Flexible Modulation of Electronic Band Structures of Wide Band Gap GaN Semiconductors Using Bioinspired, Nonbiological Helical Peptides. (2nd November 2017) - Mehlhose, Sven; Frenkel, Nataliya; Uji, Hirotaka; Hölzel, Sara; Müntze, Gesche; Stock, Daniel; Neugebauer, Silvio; Dadgar, Armin; Abuillan, Wasim; Eickhoff, Martin; Kimura, Shunsaku; Tanaka, Motomu
Abstract: Modulation of the electronic band profiles of wide band gap GaN semiconductors is achieved by the macromolecular dipole potentials exerted from ordered monolayers of synthetic, nonbiological aldehyde terminated helical peptides deposited on wet chemically oxidized GaN surfaces functionalized with aminosilanes. The selective coupling of either N‐ or C‐terminal to the amino‐terminated surface enables one to control the direction of the dipole moment, while the number of amino acids determines its magnitude. After confirming the formation of highly ordered peptide monolayers, the impact of macromolecular dipole potentials is quantified by electrochemical impedance spectroscopy. Moreover, the chronoamperometry measurements of ferrocene‐terminated peptides suggest that the transfer of electrons injected from ferrocene follows inelastic hopping, while the current responses of peptides with no ferrocene moieties are purely capacitive. Finally, the same functionalization steps are transferred to GaN/AlGaN/GaN high electron mobility transistor structures. Stable and quantitative modulation of the current–voltage characteristics of the 2D electron gas by the deposition of bioinspired peptides is a promising strategy for the macromolecular dipole engineering of GaN semiconductors. Abstract : Grafting of bioinspired but nonbiological peptides realizes the flexible modulation of the electronic band structures of GaN. The regulation of carrier mobility in 2D electron gases based on GaN/AlGaN/GaN heterostructures opens a large potential toward the macromolecular dipole engineering of GaN semiconductors without doping or deposition of inorganic materials.